Uterine myxoid leiomyosarcoma arising in a leiomyoma - A case report. - Hadzi-Nicheva, Biljana; Prodanova, Irina; Yashar, Genghis; Kubelka, Katerina; Grncharovska, Zlata; Basheska, Neli (Institute of Oncology, Sremska Kamenica, Yugoslavia, 2002)
Myxoid leiomyosarcoma of the uterus (MLU) is a very rare neoplasm. We report a case of MLU arising from a pre-existing leiomyoma. Between 1989 and 2001, 45 uterine leiomyosarcomas were diagnosed in our laboratory and MLU was established in one case only (2.1%). Subtotal hysterectomy was performed on a 56-year woman with clinical diagnosis of a uterine myoma. The histopathological processing included hematoxylin-eosin, histochemical and immunohistochemical staining of selected specimens. Macroscopically, the uterus measured 15 x 12 x 11 cm, with an indistinctly circumscribed multi-nodular tumorous mass 10.5 cm in diameter, and infiltrative satellite nodules in the surrounding myometrium. The morphology of the neoplasm showed a leiomyoma with distinct degenerative changes, necrosis and hemorrhage. In some areas the cells were round or oval with a vacuolated cytoplasm, slight atypia and rare mitoses. The mitotic count was 1-3 cells/10 HPF. Due to the presence of an abundant mucoid substance, these areas appeared as hypocellular. The additional processing confirmed the smooth muscular origin of the neoplasm (Masson trichrome, azan, desmine, alfa-smooth muscle actin and vimentine positive). The areas of the myxomatose nodules were characterized with hormone independence (estrogen and progesterone receptors negative), high proliferative activity (Ki-67 - 30%) and the presence of p53 protein product (45%). The areas of the pre-existing leiomyoma showed hormone dependence, low proliferative activity and absence of p53 protein product. Additional immunostaining is useful in supporting a diagnosis of MLU in myxoid uterine smooth-muscle tumors with a low mitotic rate.
Keywords: uterine neoplasms; leiomyosarcoma; immunohistochemistry